Congenital Smooth Muscle Hamartoma on the Face Treated Using Vascular Laser. Issue 6 (3rd September 2012) - Grillo, Emiliano; Boixeda, Pablo; Ballester, Asuncion; Vano‐Galvan, Sergio; Gonzalez, Carmen; Jaén, Pedro
<x xml:space="preserve">Abstract</x> Abstract: A congenital smooth muscle hamartoma is a rare, benign proliferation of smooth muscle bundles in the dermis that is usually diagnosed in the neonatal period or infancy. Surgical excision is the first‐line therapeutic option, but in certain areas such as the face, surgery may be too aggressive, and different treatments should be considered. We present the case of a congenital smooth muscle hamartoma on the face treated using pulsed dye laser with good response.